Is the skull of the black-headed gull dimorphic? Analysis of shape variation - P. Indykiewicz; N. Manuta; J. Bonecka; O. Gündemir; T. Szara (The European Zoological Journal, 2025)
The black-headed gull (Chroicocephalus ridibundus) is a small bird belonging to the Laridae family. Their distribution and breeding broad area primarily cover the northern part of the Eurasian continent. Gulls are considered monomorphic birds, and distinguishing the sexes based on external morphological features is extremely difficult. In this study, a 3D shape analysis of the skull of black-headed gulls from central-northern Poland was performed to reveal the variation in shape between individuals and whether male skulls differ from females. For these purposes, 82 skulls were used (32 females and 50 males). 3D surface models of the skull were extracted using computed tomography. Twenty-one landmarks were designed on each skull. The principal components method was used to assess the variability of skull shapes. The first two principal components accounted for 48.28% of the cumulative shape variation. The most significant shape variation relative to PC1 was observed in the braincase. Positive PC2 values reflected the neurocranium expanding more rapidly dorso-ventrally with a wider orbit, and the nasofrontal hinge moved dorsally. According to the Procrustes ANOVA, the centroid size was statistically different between the sexes (p < 0.0001). Male skulls were longer than females. Neurocranium was wider in male gulls. The nasofrontal hinge was more caudal in females. The results of this study are consistent with the observations of other authors applying linear morphometry.